Kebutuhan Pengembangan Layanan Bimbingan Klasikal Menggunakan Media Ular Tangga di SMP - Winasari, Desi; Suriswo, Suriswo; Nugroho, Rahmad Agung (Universitas Nusantara PGRI Kediri, 2026)
This study aims to develop a classical guidance service model that integrates traditional board game media to reduce bullying behavior among seventh-grade students at SMP Negeri 2 Tanjung, Brebes. The research employed a Research and Development (R&D) approach using the ADDIE model, which was intentionally limited to the Analysis, Design, and Development stages. The Implementation and Evaluation phases were not fully conducted, as the primary focus of the study was on the initial formulation and early development of the guidance service model. Therefore, a comprehensive evaluation of the product’s effectiveness is recommended for future research. A total of 32 seventh-grade students participated as research subjects. Data were collected through interviews, classroom observations, and questionnaires. The data analysis combined qualitative and quantitative approaches to identify students’ needs related to the developed guidance services. The findings indicate that the integration of traditional board games into classical guidance services contributes significantly to reducing bullying behavior and fostering a more positive and supportive learning environment